A Generally Applicable Approach Using Sequential Deposition to Enable Highly Efficient Organic Solar Cells. Issue 12 (13th September 2020) - Fu, Huiting; Gao, Wei; Li, Yuxiang; Lin, Francis; Wu, Xin; Son, Jae Hoon; Luo, Jingdong; Woo, Han Young; Zhu, Zonglong; Jen, Alex K.‐Y.
Abstract: Bulk‐heterojunction (BHJ) organic solar cells (OSCs) are prepared by a common one‐step solution casting of donor‐acceptor blends often encounter dynamic morphological evolution which is hard to control to achieve optimal performance. To overcome this hurdle, a generally applicable, sequential processing approach has been developed to construct high‐performance OSCs without involving tedious processes. The morphology of photoactive layers comprising a polymer donor (PM6) and a nonfullerene acceptor (denoted as Y6‐BO) can be precisely manipulated by tuning Y6‐BO layer with a small amount of 1‐chloronaphthalene additive to induce the structural order of Y6‐BO molecules to impact the blend phase. The results of a comparative investigation elucidate that such two‐step procedure can afford more favorable BHJ microstructure than that achievable with the single blend‐casting route. This translates into improved carrier generation and transport, and suppressed charge recombination. Consequently, the devices based on sequential deposition (SD) deliver a remarkable efficiency up to 17.2% (the highest for SD OSCs to date), outperforming that from the conventional BHJ devices (16.4%). The general applicability of this approach has also been tested on several other nonfullerene acceptors which show similar improvements. These results highlight that SD is a promising processing alternative to promote better photovoltaic performance and reduce production requirements. Abstract : A generally applicable sequential deposition (SD) strategy is developed to construct high‐performance organic solar cells (OSCs) without involving complicated procedures for morphological control. The SD‐processed OSCs via simple adjustment of the acceptor layer to impact the blend phase can afford higher efficiencies than their conventional OSC counterparts, providing an avenue toward promoting better photovoltaic performance and reducing production requirements.